Hacia una visión holística de la distancia en los negocios internacionales: El caso colombiano - Carolina Caicedo Marulanda; José Pla Barber; Fidel León Darder; Jhon James Mora Rodríguez (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2017)
– This article presents new estimations of the distance in international business between Colombia and 57 countries in Europe, America, Asia, Africa and Oceania. The concept of distance that we use transcends the institutional level and incorporates both institutional aspects and those that have not yet been considered in the literature such as labor market, business practice and innovation. In this way, we build a holistic distance index and discuss the results for the specific case of Colombia. Thus, from the construction of a synthetic index of distance, we calculated the distances between Colombia and the countries of the sample using the Mahalanobis distance in the dimensions analyzed here. Our results show that although there is progress in the globalization of international business between Colombia and the countries of the sample there are still restrictions faced by Colombian companies that are interested in entering these markets seeking to benefit from the free trade agreements.
Keywords: C23; D22; J25; 330; holistic distance; factor analysis; kernel density; international business